Cultural Hybridization in Christian China: The Art of Cloisonné at The Service of God - Manuel Parada López de Corselas; Alberto A. Vela-Rodrigo (Religions, 2021)
The usual conception of traditional Chinese art tends to forget the existence of a rich cultural legacy of Christian origin that has been reflected in the manufacture of ritual objects for the convert communities and European missionaries in China. Among the most used techniques, cloisonné stands out, with important liturgical or decorative pieces treasured by missionaries and collectors, many of them in Western museums today. This work tries to make an approximation to some of those ritual objects used by the Christian Chinese communities that reflect the great influence that the Western artistic models had in the conception of art as a result of the cultural hybridization between both worlds.